Evaluation of the behavior of horses used for teaching beginner riders: Review article - Gyalus, Melinda; Bene, Szabolcs; Polgár J., Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
Horse breeding abroad reached a high level, where it is recognized that besides mesuring individual performance external traits and pedigree (exterior traits) studying internal (interior) traits are of great importance as well. Unfortunately, practice in Hungary is rather conservative, as the behavior of horses is not considered as an important issue during breeding survey and exams. It is the interest of our horse breeding to give more emphasis to the study of behavioral parameters besides the conventional performance testing. Testing temperament, ride ability and docility should be done objectively and the results should be used to meet the demands of safe training, sport riding as well as hobby and therapeutic riding. When teaching beginner riders or children, the temperament and habits of the training horses – like cooperation with the trainer and the rider, the open, friendly behavior, tranquility and intelligence - are extremely important. The aim of our study was to find behavioral and temperament tests which are suitable for the preparation of a series of practical tests for the Hungarian horse breeding practice, in other words, which are able to reflect the behavior and character of horses aimed to use for the training of beginner riders. We chose and lined up different behavioral tests from the available literature to mimic the everyday life in the riding hall, modeling such basic situations which are faced by either the horses or their riders day by day.
Keywords: behavioral tests; trainer horse; external and internal traits